Cheilopallene ogasawarensis, a New Species of Shallow-Water Pycnogonid (Arthropoda: Pycnogonida) from the Ogasawara (Bonin) Islands, Japan, Northwest Pacific - Nakamura, Koichiro; Akiyama, Tadashi (Zootaxa, 2015)
A new species of pycnogonid recorded from the shallow waters of Ogasawara (Bonin) Island, Japan, Cheilopallene ogasawarensis n. sp. is described, illustrated and compared with similar species. Cheilopallene ogasawarensis is only the third pycnogonid species recorded from these islands. Morphological characters clearly distinguish the new species from its geographically closest congener C. nodulosa Hong and Kim, 1987, also recorded from Japanese waters.